Designing health promoting foods for the ageing population: a qualitative approach. Issue 12 (7th December 2015) - Collins, Orla; Bogue, Joe
Abstract : Purpose: – The purpose of this paper is to gather stakeholder tacit knowledge to design new product concepts with optimal product attributes for new health promoting food products for the ageing population. Design/methodology/approach: – This research employed a qualitative research method. A total of 16 in-depth interviews were carried out to identify key product design attributes. These attributes were used to design health promoting foods for the ageing population. Findings: – Age-related conditions affect and alter the design of health promoting foods targeted at the ageing population. Providing the ageing consumer segment with access to health promoting foods facilitates positive ageing intervention. The integration of affordability and convenience elements into ageing food design attributes is important for product acceptance. The multi-level demands and heterogeneity of ageing consumers result in the need for a variety of nutritionally tailored food formats. A dairy-based beverage was considered to be the optimal product concept for the ageing population. Research limitations/implications: – The inclusion of stakeholders from the food industry could result in levels of food industry bias. The sample size of stakeholders was limited to 16 participants. One interview guide was used throughout all interviews to ensure consistency levels. A more flexible instrument may have captured more specific stakeholder information. Practical implications: – During the early stages of the new product development process, a market-oriented research methodology can help to optimise product design in terms of product attributes that drive consumer acceptance. Originality/value: – This paper provides important insights into the significance of stakeholder tacit knowledge generation throughout the need identification stage of the NPD process. Specifically this paper provides stakeholder tacit knowledge on the optimal design of health promoting foods for the ageing population. This knowledge has the ability to provide market-oriented information on health promoting food concepts which can be valuable for food manufacturers to maximise NPD performance, create value and develop competitive advantage within their marketplace. Finally, design templates of health promoting foods for the ageing population are of high strategic importance to food manufacturers, governments, health professionals and medical professionals.